Sporadic malignant peripheral nerve sheath tumour in a 3-year-old girl: A diagnostic challenge - Mustapar, Nurulhasanah; Ismail, Ismaliza; Wan Sulaiman, Wan Azman; Wan Ismail, Wan Faisham Nu’man; Tuan Sharif, Sharifah Emilia (Malaysian Journal of Pathology, 2018)
Introduction: Malignant peripheral nerve sheath tumour (MPNST) is an uncommon malignant neoplasm of childhood with unfavourable prognosis. Only 1.7% of the cases have been reported in children less than five years of age and approximately one-half arise from a benign peripheral nerve sheath tumour especially in background of neurofibromatosis type 1 (NF1). Primary MPNST in children are even rarer. Case Report: A 3-year-old Malay girl presented with painful right axillary swelling for 6 months duration, initially treated as axillary lymphadenitis and she defaulted follow up. She came back 4 months later with enlargement of the swelling. The biopsy was reported as Schwannoma which correlates with MRI findings of benign peripheral nerve sheath tumour. Final diagnosis after debulking surgery was consistent with MPNST. She succumbed to death 20 months after her initial diagnosis of advanced MPNST and lung metastasis. Pathological findings: Grossly, a huge partlycircumscribed soft tissue mass noted arising from a nerve with solid greyish yellowish myxoid cut surface. Spindle shaped cells arranged in herringbone pattern with marked pleomorphism, brisk mitosis and extensive necrosis are seen microscopically. Immunohistochemistry shows patchy S100 protein staining with loss of expression of H3K27 trimethylation. Conclusion: Although MPNST is rare in paediatric age group, diagnosis should be considered in children without NF1 with rapidly evolving and painful mass in the distribution of a peripheral nerve. In this case, the diagnosis was delayed and made after surgery. Due to its morphologic heterogeneity and lack of specific immunohistochemical markers, MPNST remains a diagnostic challenge.